Relative importance of professional practice and engineering management competencies. (2nd September 2016) - Pons, Dirk
ABSTRACT: Problem : The professional practice of engineering always involves engineering management, but it is difficult to know what specifically to include in the undergraduate curriculum. Approach : The population of New Zealand practising engineers was surveyed to determine the importance they placed on specific professional practice and engineering management competencies. Findings : Results show that communication and project planning were the two most important topics, followed by others as identified. The context in which practitioners use communication skills was found to be primarily with project management, with secondary contexts identified. The necessity for engineers to develop the ability to use multiple soft skills in an integrative manner is strongly supported by the data. Originality: This paper is one of only a few large-scale surveys of practising engineers to have explored the soft skill attributes. It makes a didactic contribution of providing a ranked list of topics which can be used for designing the curriculum and prioritising teaching effort, which has not previously been achieved. It yields the new insight that combinations of topics are sometimes more important than individual topics.